Women's empowerment in Ghana's agriculture sector: Insights from the Women's Empowerment in Agriculture Index - Abdu, Aishat; Malapit, Hazel J.; Go, Ara (International Food Policy Research Institute, 2025)
Key messages • Gender disparities in agriculture persist in Ghana, particularly in land ownership, credit access, and decision-making power, limiting women’s productivity and contribution to food security. • The Women’s Empowerment in Agriculture Index (WEAI) has been instrumental in revealing these gender gaps in northern Ghana, but similar data are lacking for other regions, hindering national-level policy responsiveness. • Targeted interventions, such as securing land rights for women, improving access to financial services, and promoting participation in farmer-based organizations, are critical to advancing women’s empowerment and achieving gender-equitable agricultural development.